The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1038/cdd.2008.160
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth suppression by thanatos-associated protein 11(THAP11) is mediated by transcriptional downregulation of c-Myc

Abstract: Thanatos-associated proteins (THAPs) are zinc-dependent, sequence-specific DNA-binding factors involved in cell proliferation, apoptosis, cell cycle, chromatin modification and transcriptional regulation. THAP11 is the most recently described member of this human protein family. In this study, we show that THAP11 is ubiquitously expressed in normal tissues and frequently downregulated in several human tumor tissues. Overexpression of THAP11 markedly inhibits growth of a number of different cells, including can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 39 publications
6
50
1
Order By: Relevance
“…Previous studies have shown two members of the same family, THAP1 and THAP11, can regulate cell proliferation (6,52). Furthermore, genetic studies using C. elegans support a role of THAP proteins in cell cycle regulation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies have shown two members of the same family, THAP1 and THAP11, can regulate cell proliferation (6,52). Furthermore, genetic studies using C. elegans support a role of THAP proteins in cell cycle regulation.…”
Section: Discussionmentioning
confidence: 84%
“…THAP5 has an atypical zinc finger domain at its amino terminus that could bind to specific DNA sequences on different promoters. A recent study showed that another member of the same family, THAP11, could inhibit cell cycle by binding to the promoter of c-Myc and downregulating its expression (52).…”
Section: Discussionmentioning
confidence: 99%
“…Individual THAP proteins have been implicated in a diverse array of physiological processes, including cell proliferation, regulation of transcription, apoptosis, and maintenance of embryonic stem (ES) cell pluripotency (2,3,6,9,12,24,33,45). The DNA-and HCF-1-binding properties of THAP proteins naturally suggest that these proteins may regulate normal or disease-specific physiological processes in a DNA-and chromatin-dependent manner.…”
mentioning
confidence: 99%
“…The majority of conserved THAP proteins also contain a coiled-coil protein interaction domain adjacent to a host cell factor 1 (HCF-1)-binding motif (HBM) (26). The tetrapeptide HBM (E/DHXY, where X is any amino acid) facilitates the interaction of THAP proteins and other DNA-binding factors with the Kelch domain of HCF-1, a transcriptional coregulator and cell proliferation factor associated with a variety of enzymatic and histone-modifying activities, including SIN3/HDAC histone deacetylase, SET1/MLL histone methyltransferase, and MOF histone acetyltransferase (11,22,23,26,30,39,42).Individual THAP proteins have been implicated in a diverse array of physiological processes, including cell proliferation, regulation of transcription, apoptosis, and maintenance of embryonic stem (ES) cell pluripotency (2,3,6,9,12,24,33,45). The DNA-and HCF-1-binding properties of THAP proteins naturally suggest that these proteins may regulate normal or disease-specific physiological processes in a DNA-and chromatin-dependent manner.…”
mentioning
confidence: 99%
“…Twelve THAP proteins have been identified in humans (THAP0 to THAP11). Individual THAP proteins are involved in different physiological processes, including cell Brought to you by | MIT Libraries Authenticated Download Date | 5/11/18 7:43 PM proliferation, regulation of transcription, apoptosis, and the maintenance of embryonic stem cell pluripotency [96][97][98][99][100]. THAP proteins in association with HCF-1 may function in chromatin-dependent processes, and aberrant regulation of these proteins may be involved in many diseases, including cancer.…”
Section: Ogt and Hcf-1mentioning
confidence: 99%